THE INSERTION OF DISTAL FEMORAL INTERLOCKING SCREWS: FREHAND ANTEROPOSTERIOR VIEW VERSUS LATERAL VIES TECHNIQUE - Naeemullah; Faaiz Ali Shah; Mian Javed Iqbal; Ali, Mian Amjad (Journal of Postgraduate Medical Institute, 2024)
Objective: To compare the freehand anteroposterior view technique for the insertion of distal femoral interlocking screws with the lateral view technique in term of success rate, time required and the number of fluoroscopic shots. Methodology: This Quasi-experimental study was conducted in Orthopedic division Lady Reading Hospital Peshawar from 4th October 2022 to 05th August 2023. In group “A” both the distal locking screws of the interlocking nail femur were inserted under C-arm using freehand anteroposterior view technique while in group “B” conventional freehand lateral view technique was used. The success rate of distal screw insertion was determined using Rohilla and Singh criteria. The time taken for screw insertion and number of C-arm shots was compared in both groups. Results: The total number of patients were 186. Each group A and B had 93 patients each. No failure of screw insertion was noted in group A while in group B failure was noted for distal screws in 23 (24.73%) and for proximal screws in 15 (16.12%) patients (p<0.05). In group A the average time required for the insertion of distal interlocking screw was 6.4 ± 1.3 minutes in group A and 16.9 ± 1.5 minutes in group B (p<0.05).The average number of C-arm shots were 5.4 ± 1.7 for inserting distal interlocking screws in group A while 15 ± 1.2 shots were used for the insertion of distal interlocking screw in group B (p<0.05). Conclusion: We achieved successful insertion of the distal femoral interlocking screws with freehand technique in anteroposterior view in majority of our patients. The technique took less time and less radiation exposure than conventional lateral view technique.